The behavior of graphene-nanoplatelets-based high-performance concrete under ambient curing. (January 2023) - Ismail, Fouad Ismail; Shafiq, Nasir; Abbas, Yassir M.; Ateya, El Sayed; Zahid, Muhammad; Bheel, Naraindas; Benjeddou, Omrane; Abdulkadir, Isyaka
Abstract: The primary objective of this study was to evaluate the effect of GnP on the hydration and mechanical properties of HPC at ambient curing conditions. This research focused on the properties of HPC mixes containing various dosages of GnP [0.00 (control mix), 0.02, 0.05, 0.10, 0.30, and 0.50 % wt.]. The first phase involved monitoring the hydration behavior of GnP-HPC using Fourier-transform Infrared spectroscopy. Another aspect of GnP-HPC was its mechanical behavior (compressive, tensile, flexural, and modulus of elasticity). These responses were evaluated in accordance with ASTM C39, JSCE, ASTM C293, and ASTM C469 at various ages (3, 7, 28, 56, and 90 days). The current data was additionally used to evaluate the reproducibility of the ACI 318, ACI 363, and EC-2 formulas, as well as those proposed in earlier research. This research program also developed formulas for predicting GnP-HPC strength properties using a variety of nano-reinforcement materials, and its effectiveness was evaluated based on present and independent data. Test results show that the incorporation of GnP increased HPC's carbonization degree. Moreover, 0.02 % GnP improved compressive, tensile, and flexural strengths by 20.8, 30.0, and 13.2 %, respectively. Moreover, the modulus of elasticity increased by 21.7 % for the same GnP concentration. It was concluded that the models developed for relationships among various properties of GnP-HPC; modulus of elasticity, tensile strength, and flexural strength was found reliable. Predicted results were obtained up to 90 % of the experimental results in many cases.